2017
DOI: 10.1002/isd2.12006
|View full text |Cite
|
Sign up to set email alerts
|

The role telecentres play in providing e‐government services in rural areas

Abstract: In this paper, we explore the role played by telecentres for providing e-government services in rural areas. We do so by reporting from a longitudinal multiple case from Tanzania, one of the least urbanised African countries with only 23% of the population living in urban areas.Telecentres are proposed to operate as multipurpose community information and communication technology access centres offering e-government services (as well as other services), providing information, transactions, and entitlements. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 32 publications
0
13
0
1
Order By: Relevance
“…Finally, in addition to individual‐level device distributions, another common government approach to improving digital access has been to fund devices and Internet access at public community centers. Scholarship from around the globe has found that such centers can provide critical resources, especially in areas of the world where household‐level telecommunications infrastructure is lacking (Furuholt & Saebø, 2018; Rahman, 2016; Soriano et al, 2018; Uys & Pather, 2016). However, this approach also has its limitations.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…Finally, in addition to individual‐level device distributions, another common government approach to improving digital access has been to fund devices and Internet access at public community centers. Scholarship from around the globe has found that such centers can provide critical resources, especially in areas of the world where household‐level telecommunications infrastructure is lacking (Furuholt & Saebø, 2018; Rahman, 2016; Soriano et al, 2018; Uys & Pather, 2016). However, this approach also has its limitations.…”
Section: Literature Review Resultsmentioning
confidence: 99%
“…According to Benjamin (2001) and Heeks (2002), PACs are made up of several structural components (human, political and technical) that need to work together in order to achieve a functional telecentre. The lack of synergy among these components often results in poor infrastructure or the deployment of complex technologies which fail to contextualize the provision of ICTs to meet specific needs (Mutula 2010;Bois, Chigona, and Garbutt 2018;Furuholt and Saebø 2018). Access to technology and the use of technology by people of the PAC are important for measurable and non-measurable benefits to be realized (Uys and Pather 2020).…”
Section: Public Access Centres (Pacs)mentioning
confidence: 99%
“…Telecenter diusulkan untuk beroperasi sebagai pusat TIK masyarakat multiguna yang menawarkan layanan pemerintahan (e-government), menyediakan informasi transaksi dan hak pelayanan publik masyarakat lainnya [14]. Hal lain yang perlu diketahui, bahwa telecenter merupakan inisiatif nirlaba berbentuk akses publik ke komputer dan internet dengan tujuan pengembangan masyarakat [15].…”
Section: Bahan Dan Metodeunclassified